2014
DOI: 10.1016/j.brainres.2014.05.029
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cells as cellular vectors for pediatric neurological disorders

Abstract: Lysosomal storage diseases are a heterogeneous group of hereditary disorders characterized by a deficiency in lysosomal function. Although these disorders differ in their etiology and phenotype those that affect the nervous system generally manifest as a profound deterioration in neurologic function with age. Over the past several decades implementation of various treatment regimens including bone marrow and cord blood cell transplantation, enzyme replacement, and substrate reduction therapy have proved effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 202 publications
(213 reference statements)
1
13
0
2
Order By: Relevance
“…For example, exosomes from mesenchymal stromal cells contain a number of miRNAs, including miR-451, miR-1202, miR-630, miR1207-5p, miR-33b, miR-1268, miR-638, miR-575, and miR-1225-5p [130]. Whether exosomal miRNAs from bone marrow stromal cells regulate hematopoiesis in vivo is currently unknown.…”
Section: Mirnas Regulating Cell Signaling and Other Targets In Hsc Anmentioning
confidence: 99%
“…For example, exosomes from mesenchymal stromal cells contain a number of miRNAs, including miR-451, miR-1202, miR-630, miR1207-5p, miR-33b, miR-1268, miR-638, miR-575, and miR-1225-5p [130]. Whether exosomal miRNAs from bone marrow stromal cells regulate hematopoiesis in vivo is currently unknown.…”
Section: Mirnas Regulating Cell Signaling and Other Targets In Hsc Anmentioning
confidence: 99%
“…Mesenchymal stem cells (MSCs), a type of adult stem cell initially identified in bone marrow, are known to possess potent angiogenic, anti‐inflammatory, and immunomodulatory activities that are largely paracrine in nature and are being evaluated in human clinical trials to treat a diverse array of non–skeletal‐related diseases. Consistent with these findings, MSC‐based therapies have yielded benefits in rodent models of storage diseases by restoring deficient enzyme levels, reducing inflammation, and promoting survival of neural cell types . We previously demonstrated that MSCs administered via the intracranial route into healthy infant rhesus macaques exhibited low levels of durable cell engraftment and distributed nonrandomly along the brain neuraxis throughout both brain hemispheres, without producing adverse effects on the health or social, behavioral, cognitive, or motor abilities of animals up to 6 months post‐transplant .…”
Section: Introductionmentioning
confidence: 66%
“…Mesenchymal stem cells (MSCs), a type of adult stem cell initially identified in bone marrow, are known to possess potent angiogenic, anti-inflammatory, and immunomodulatory activities that are largely paracrine in nature [18][19][20][21][22] and are being evaluated in human clinical trials to treat a diverse array of non-skeletalrelated diseases. Consistent with these findings, MSC-based therapies have yielded benefits in rodent models of storage diseases by restoring deficient enzyme levels, reducing inflammation, and promoting survival of neural cell types [23].…”
Section: Introductionmentioning
confidence: 99%
“…There are suggestions that MSCs support wound healing and tissue regeneration through vessel forming and inhibition of apoptosis. More clinical trials are underway and are needed to evaluate the safety, feasibility and efficacy of CB/CT-derived MSCs as a delivery mechanism for cellular therapy in a variety of applications-for example, malignancies [64]; neurologic disorders [65,66]; primary biliary and decompensated cirrhosis; myocardial and neuronal ischemia; bone disease; connective tissue, skin and cartilage repair; and in autoimmune diseases such as lupus and rheumatoid arthritis. An improved understanding of the biology of CB/CT-derived MSCs in vivo may allow further broadening of applications.…”
Section: Discussionmentioning
confidence: 99%